11/22/63: [роман] / Стивен Кинг ; [перевод с английского В. А. Вебера] - Кинг Стивен (Король на все времена, 2018)
Экземпляры: аб. (2018) / Инвентарный номер: 54617 / Цена: / Сис.шифр: 84(7Сое) / Авт.знак: К 41 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-445